Pink Stockings, Yellow Stockings: the Use of Pink-Yellow in Marston and Shakespeare - Anita BUTLER (E-REA)
John Marston (c. 1576-1634), William Shakespeare’s younger contemporary, wrote plays such as The Malcontent (c. 1604) that are performed today: his satirical comedy What You Will (published 1607) is not one of these. Fragmentary in style and dense with satire that is largely opaque for modern audiences, the play mainly garners scholarly attention due to its association with Shakespeare’s Twelfth Night, or What You Will, with evidence suggesting that both plays were written in 1601-1602. Similarities in titles and plots have been noted, but, to date, the use of coloured stockings in both plays (pink for Marston, yellow for Shakespeare) has been overlooked. Marston’s use of pink colour in extant drama of the period presents a curious incident in chromatic history: other dramatists do not use it until the mid 17th century. How, then, can we account for Marston’s “pink”? This article argues that focus on the plays’ composition date, while using the arguably trivial lens of pink/yellow stockings, can illuminate the contemporary meaning of a word and its emergence as a colour in early modern England, and provide insights into the dramatists’ relationship during the Theatre Wars that flared briefly on the cusp of the Elizabethan-Jacobean period.